Slovakia: Security Policy Determinants (Czech Journal of International Relations, 1994)
The Minister of Foreign Affairs of Moravčík's interim government, E. Kukan, declared two weeks before the early parliamentary elections that Slovakia's foreign policy was presented in such a significant way in international relations that it was impossible to change its direction and character. "Every government that takes office after the elections will continue it," he said. The same, and perhaps with an even greater degree of persuasiveness, should also apply to security policy. In consolidated democracies, both belong to the areas whose concept the majority of political parties accepted by consensus.Even though Slovakia is far from belonging to this category of states, it does not have many alternative solutions to its security problems.If a country's security policy is to optimally correspond to its national interests, it must consistently respect basic geopolitical realities. The constant factors that determine Slovakia's security policy are so influential and striking that none of the parliamentary political parties can ignore them if they want to share in power. From the election programs of those who exceeded the set threshold and whose deputies took seats in the National Council of the Slovak Republic, it follows that these factors, apart from the CIS, perceive these factors very intensively.